Catalytic pyrolysis of Oil Palm Frond (OPF) using Graphite Nanofiber (GNF) as catalysts - Wai, C.K. (Italian Association of Chemical Engineering - AIDIC, 2015)
This paper focuses on exploring the application of Graphite Nanofiber (GNF) as a carbon allotropes catalyst in thermal pyrolysis of Oil Palm Frond (OPF) with the hope of breakthrough in replacing conventional Zeolite ZSM-5 catalyst. The present study primarily highlights on the bright potential of GNF catalyst in producing high quantity of bio-oil, along with excellent thermal decomposition performance as a carbon based catalyst. In this paper, the thermal pyrolysis is conducted in a semi batch pyrolysis reactor which externally heated by an electrical vertical split tube furnace. 15 g of OPF biomass is thermally decomposed at three distinct temperatures of 573K, 673K and 773 K and catalyst loadings of 1 wt, 5 wt and 12 wt. The nitrogen gas flow rate and heating rate are kept constant at 60 mL/min and 20 °C/min. Comprehensive evaluation of the catalyst performances in term of pyrolysis oil yields are performed at various reaction temperatures and catalyst loadings in thermal pyrolysis of OPF. The superior results obtained revealed OPF biomass can be an excellent biomass feedstock in producing excellent quantity of bio-oil with oil yield as high as 46.04 ± 1.77 wt at a mild reaction temperature of 673K and catalyst loading of 1 wt. On the other hand, the highest solid residue yield is obtained at 5 wt catalyst loading and temperature of 573 K, mainly due to incomplete decomposition of the biomass structure. In conclusion, as the pyrolysis temperature increases, the bio char yield decreases with significant trend, leaving high pyrolysis oil yield and low quantity of char residue. Copyright © 2015, AIDIC Servizi S.r.l.,.